Gut Microbiota in a Viral Model of Multiple Sclerosis: Modulation and Pitfalls by Oral Antibiotic Treatment - Ijaz Ahmad; Seiichi Omura; Sundar Khadka; Fumitaka Sato; Ah-Mee Park; Sandesh Rimal; Ikuo Tsunoda (Cells, 2025)
Viral infections have been associated with multiple sclerosis (MS), an immune-mediated disease in the central nervous system (CNS). Since Theiler’s murine encephalomyelitis virus (TMEV) can induce MS-like demyelination, TMEV infection is the most widely used viral model for MS. Although the precise pathophysiology is unknown, altered fecal bacterial populations were associated with distinct immune gene expressions in the CNS. We aimed to determine the role of gut microbiota in TMEV infection by administering an antibiotic cocktail in drinking water before (prophylactic administration) or after (therapeutic administration) TMEV infection. The antibiotic administration reduced total eubacteria, including the phyla Bacillota and Bacteroidota, but increased the phylum Pseudomonadata in feces. Prophylactic administration did not alter TMEV-induced inflammatory demyelination clinically or histologically, without changes in anti-viral IgG1/IgG2c levels or lymphoproliferative responses; therapeutic administration temporarily suppressed the neurological signs. Although antibiotic treatment had minimal effects on TMEV infection, adding metronidazole and ampicillin in drinking water substantially reduced water intake in the antibiotic group of mice, resulting in significant body weight loss. Since dehydration and stress could affect immune responses and gut microbiota, caution should be exercised when planning or evaluating the oral antibiotic cocktail treatment in experimental animals.